Досягнення і перспективи співпраці українського та німецького університетів - Тревого, І.; Задорожний, В.; Савчук, Н.; Trevoho, I.; Zadorozhnyi, V.; Savchuk, N. (Видавництво Львівської політехніки, 2025)
Подано інформацію про нові заходи співпраці Інституту геодезії Львівської політехніки і факультету ланд- шафтної архітектури, геоматики і геодезії Університету прикладних наук (м. Нойбранденбург, Німеччина), яка успішно продовжується майже 20 років. Увага зосереджена на особливостях навчально-наукової геодезичної практики українських студентів, підготовки та навчання за програмою подвійних дипломів студентів-магістрів Інституту геодезії в німецькому університеті

Information about new cooperation activities between the Institute of Geodesy of Lviv Polytechnic and the Faculty of Landscape Architecture, Geomatics and Geodesy of the University of Applied Sciences (Neubrandenburg, Germany), which has been successfully continuing for almost 20 years. Attention is focused on the features of the educational and scientific geodetic practice of Ukrainian students, training and education under the double diploma program of master's students Institute of Geodesy at a German university
Achievements and prospects of cooperation between Ukrainian and German universities
Keywords: геодезія; геоінформатика; наувчально-наукова практика; програма подвійних магістерських дипломів; міжнародна співпраця в сфері освіти і науки; взаємний обмін досвідом; geodesy; geoinformatics; teaching and scientific practice; double master’s degree program; international cooperation in education and science; mutual exchange of experience; 528.24